Papua New Guinea : Request for a Staff-Monitored Program; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
Papua New Guinea (PNG) is a fragile state, vulnerable to recurrent shocks. A third wave of the COVID-19 pandemic is straining the healthcare system. Widespread vaccine hesitancy has contributed to very low uptake of the vaccines with about only 2 percent of the population fully vaccinated. Real GDP is estimated to rebound modestly to grow by 1.7 percent in 2021 after the downturn in 2020. Elections are due to take place in June 2022, and the formal campaign period will commence by end-April.